Value engineering analysis of the green semesta housing project in Semarang - Faza, Muhammad Arief; Antonius, Antonius; Wibowo, Kartono (Trigin Publisher, 2025)
The demand for housing continues to rise along with the growing population. Housing development is one of the efforts to meet society's need for residential homes. The Green Semesta housing project in Semarang offers Type 36 and Type 45 houses. However, given the vast area of Semarang and the intense competition among housing developers offering higher-segment housing at similar price ranges, it can be concluded that there is cost inefficiency in the construction of this project. Therefore, a solution is needed to address this issue by applying Value Engineering. This study aims to analyze the optimization of the cost budget plan without compromising the quality and functionality of the buildings using the Value Engineering method.This method compares the cost advantages of the landscape design before and after redesign by modifying the house layout, appearance, and the number and composition of houses/site plans to achieve maximum benefits. This analysis follows the stages of Value Engineering Planning, which include the information stage, creative stage, analysis stage, recommendation stage, and presentation stage. Based on the results of the Value Engineering analysis of the Green Semesta Housing Project in Semarang, the most profitable design alternative is Design B, which involves modifying the number of Type 45 units from 21 to 9 and increasing the Type 36 units from 16 to 31. After the redesign, the production cost for Type 45 units decreased from IDR 135,254,167.70 to IDR 124,656,875,91, while the original cost for Type 36 units decreased from IDR 96,224,877.00 to IDR 93,086,166.00.